2019
DOI: 10.3390/ijerph16091577
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School-Related Well-Being for Adolescent Subjective Health Complaints

Abstract: Background: This study aimed to explore the prevalence of chronic specific-site and multisite pain in adolescents and to investigate how it can possibly be determined by school-related factors. Methods: A population-based cross-sectional study was conducted in 2014 in Lithuania as a Health Behavior in School-Aged Children (HBSC) survey. The sample consisted of 5730 school children, aged 11, 13, and 15 years. The analyzed data focused on the school-related context (relations with family, peers, and teachers; sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…However, there were statistically significant differences between repeating a year and neuroticism (p = 0.043), as well as anti-social behaviour (p = 0.046). These subjects define themselves as anxious, troubled, fearful to change, and prone to mood swings and depression [50], which may correspond to some of the feelings reported in studies conducted in repeaters. Many studies have already demonstrated a correlation between anti-social behaviour and being a repeater [51], and some authors even suggest a possible prediction of criminal behaviour [52].…”
Section: Discussionmentioning
confidence: 76%
“…However, there were statistically significant differences between repeating a year and neuroticism (p = 0.043), as well as anti-social behaviour (p = 0.046). These subjects define themselves as anxious, troubled, fearful to change, and prone to mood swings and depression [50], which may correspond to some of the feelings reported in studies conducted in repeaters. Many studies have already demonstrated a correlation between anti-social behaviour and being a repeater [51], and some authors even suggest a possible prediction of criminal behaviour [52].…”
Section: Discussionmentioning
confidence: 76%
“…However, PHC in adolescents has not attracted much scientific attention in Lithuania, despite the relatively high overall prevalence of youth psychiatric disorders compared with Western European countries [14]. Therefore, the analysis of the factors associated with Lithuanian adolescents’ psychosocial well-being and lifestyle factors is very important [15]. To the best of our knowledge, this is one of the first studies to address this question in Lithuania.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, school nurses say that the school nurse's office and the waiting room can be like an oasis at school for students with mental illness (Jonsson et al, 2017). A school environment where students experience participation, support, and feel safe and comfortable has shown a connection to better self-reported student health (Vaičiūnas & Šmigelskas, 2019;Warne et al, 2017).…”
Section: Metaparadigm Of Nursing Theory-the Second Component In the Holistic Nursing Theorymentioning
confidence: 99%